The Legal Status of Personal Prelature According to the Documents Issued by Pope Francis in 2022-2023. Part I - Dawid Pietras (Kościół i Prawo)
A personal prelature was an ecclesiastical circumscription (complementary community). Its establishment was proposed during the Second Vatican Council. Its aim was to ensure the proper distribution of the clergy and to respond to new pastoral challenges. Its legal status was significantly changed by Pope Francis’s motu proprio of August 8, 2022. By amending the canons of the 1983 Code of Canon Law (can. 294-297), the Roman Pontiff equated this personal structure with a public clerical association of the faithful under the pontifical right. As a result, a personal prelate lost his position as an Ordinary and became a Moderator with the faculties of an Ordinary. The lay faithful who cooperate with a personal prelature are now subject only to the jurisdiction of a local Ordinary. The Dicastery for the Clergy assumed the competences over a personal prelature. The Statutes of the only Personal Prelature of Opus Dei established so far will have to be adapted to the new norms.